Energetics and Electronic Properties of Interstitial Chlorine in CdTe. Issue 3 (9th October 2018) - Orellana, Walter; Menéndez‐Proupin, Eduardo; Flores, Mauricio A.
Abstract : The role of interstitial chlorine in the electronic properties of CdTe is addressed by density functional theory calculations including hybrid functionals and large unit cells. The stability and diffusion energy barriers of the impurity are analyzed as a function of the Fermi level position in the band gap. Chlorine is found to be stable in at least five interstitial sites with rather close formation energies, suggesting that they are all probable to be found. In p ‐type CdTe, the most stable sites are at the center of a CdTe bond and at a split‐interstitial configuration, both acting as shallow donors. Whereas in n ‐type CdTe, it is found at the tetrahedral site surrounded by Cd hosts, acting as a shallow acceptor. We also find that chlorine can induce a deep acceptor level in the bandgap after binding with three Cd host atoms, which can explain the experimentally observed high resistivity in Cl‐doped CdTe. The energy barriers for chlorine diffusion in both p ‐type and n ‐type CdTe are also discussed. Abstract : Interstitial chlorine in CdTe is found stable in at least five interstitial sites with close formation energies, acting as shallow acceptor, shallow donor and also as a deep‐level recombination center that can explain the observed high resistivity in Cl‐doped CdTe. This DFT study highlights the influence of p‐type and n‐type doping characteristics in the stability and diffusion properties of chlorine.